2016
DOI: 10.1530/erc-16-0258
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid neoplasms after chemotherapy and PRRT: myth and reality

Abstract: Peptide receptor radionuclide therapy (PRRT) with 90 Y-octreotide or 177 Lu-octreotate is an effective treatment for inoperable or metastatic neuroendocrine tumors (NETs), particularly well-differentiated gastroenteropancreatic or bronchopulmonary NETs. PRRT is generally extremely well tolerated, with modest toxicity to target organs, kidney and bone marrow. Nevertheless, a priori concerns regarding long-term effects lead clinicians such as Brieau and coworkers, in this ERC issue, to ascribe to the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 48 publications
3
19
0
1
Order By: Relevance
“…The spectrum of permanent myelotoxicity ranges from reduction of bone marrow reserve to secondary myeloproliferative diseases (myelodysplastic syndrome and leukaemia) but these are rare (approximately 2%). They do not occur more frequently than with other myelotoxic treatments [232][233][234].…”
Section: Peptide Receptor Radionuclide Therapymentioning
confidence: 86%
See 1 more Smart Citation
“…The spectrum of permanent myelotoxicity ranges from reduction of bone marrow reserve to secondary myeloproliferative diseases (myelodysplastic syndrome and leukaemia) but these are rare (approximately 2%). They do not occur more frequently than with other myelotoxic treatments [232][233][234].…”
Section: Peptide Receptor Radionuclide Therapymentioning
confidence: 86%
“…Acute side effects include mild nausea (25% of patients) and vomiting related to the co-administered nephro-protective amino acid infusion (in up to 10%) [231]. Subacute effects include mild to moderate fatigue, mild alopecia and mild hematologic toxicity (WHO grades 1 or 2) transiently in 85-90% of patients [232]. Severe (grades 3 and 4) toxicity occurs in 10-15% irrespective of the type of radiopeptide used; this is usually reversible and very rarely requires transfusion or granulocyte support [231].…”
Section: Peptide Receptor Radionuclide Therapymentioning
confidence: 99%
“…In lower-grade NETs, which would be expected to have longer survival independent of therapeutic effects, the potential benefits of chemotherapy need to be balanced against the risks of inducing MDS or leukaemia, which may be more likely when an alkylating agent like temozolomide is used [53]. A recent report from France, where alkylating agents are widely used in chemotherapy regimens, indicated that 20% of patients receiving PRRT as a salvage therapy developed MDS [54] but these data have been disputed by a more comprehensive review of the experience with PRRT from multiple international trials and reported case series [55]. The overall risks of MDS and leukaemia appear to be low (<2%) with PRRT, as described in a recent comprehensive review of the literature [56].…”
Section: Netter-1: the First Randomized Controlled Trial Of Prrtmentioning
confidence: 99%
“…Long-term myelotoxicity in the form of myelodysplastic syndrome or acute leukemia is a rare and severe adverse event associated with PRRT, occurring in 1%-2% of patients (29). Incidence rates are higher in patients who have been heavily pretreated with alkalizing chemotherapeutics, probably reflecting the myelotoxic properties of these agents (30,31). …”
Section: Safetymentioning
confidence: 99%